The Comparison of Level and Pattern of Attention Demands in a Volleyball Jumping Serve - Hanid Salehi; Ahmadreza Movahedi; Gholamali Ghasemi Kahriz Sangi; Adnan Ghazanfari (University of Tehran, 2011)
The aim of this investigation was to compare the level and the pattern of attention demands of a volleyball jumping serve using a probe reaction time (RT) technique. 14 junior elite volleyball players performed 60 jumping serves (JS) with their preferred hand. Jumping serve was performance as the primary task and verbal RT that was administered in four probe positions (PP) as secondary task. Results indicated a non-linear attention pattern in the performance of jumping serve so that probe RT was highest in pre-shot in run up (PP1) and in landing (PP4) while it was lowest in pre-jump stepping ahead (PP2) and pre-striking (PP3). According to the results, attention level in failed serves was lower than successful ones while the attention pattern was similar. It was concluded that attention deficit might be one reason for failing serves.